(untitled) (Eurasian Journal of Research, Development and Innovation, 2023)
The growth of the invasive pike-perch (Sander lucioperca), an important commercial fish in the Tudakul reservoir, was studied. A positive linear relationship (v=0.7985*SL+14.819; r=0.69) was revealed between scale sizes (v, eyepiece-micrometer units) and standard body length (SL, cm). The samples included fish with a total length of 17–64.2 cm, standard length 14.2 – 54.2 cm, body weight 38 – 2420 g at the age of 1–4 years. The dependence of the standard and total (TL, cm) body lengths could be characterized by the regression equation: SL = 0,9181*TL - 1,7941 (r = 0,99). Total body weight (W, g) is related to total and standard body length: w = 0,00228*TL3,3751 (r=0,93) and w = 0,0069*SL3,186 (r=0,93). The average growth rate of pike-perch: SL1 -22.8 cm, SL2 – 40.6 cm, SL3 – 54.0 cm, SL4 -63 cm.